Evaluation of Antioxidant and Anti Bacterial Activity of Polyherbal Formulation Allium Ophioscorodon - Ganiwada, Bhargavi; Pavan, J.N. Venkat; Poojitha, M.; ManoharBabu, S. (Asian Journal of Pharmaceutical Research and Development, 2017)
The active properties of poly herbal formulation Allium ophioscorodon contain not less than 0.2% of allicin which enhances the microbial and antioxidant activity. The allicin in raw garlic has been shown to kill 23 types of bacteria .At present study an attempt was done on Allium ophioscorodon to extract by hand power rotation by ethanol and separated by centrifugation at 3000 rpm and the filtrate was collected and stored at -4 0 c, phytochemical tests, anti-bacterial activity by disc diffusion method, in vitro antioxidant activity by hydrogen peroxide scavenging method were done.